2009
DOI: 10.2147/ndt.s4271
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy or monotherapy for the depressed type of schizoaffective disorder

Abstract: Several studies have demonstrated the effectiveness of adjunctive antidepressant drug therapy to improve the depressive or negative symptoms of schizoaffective disorder, however, monotherapy with atypical antipsychotics may be advantageous. We compared the effi cacy and safety of risperidone monotherapy versus combination therapy of haloperidol with sertaline for the acute treatment of schizoaffective disorder, depressed type. This is an open label study of 52 female inpatients randomly assigned to risperidone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Thus, MS have been found to reduce relapses and hospitalizations (Greil et al ., 1997; Maj, 1988), to associate with lower total PANSS scores, and less negative and cognitive symptoms (Small et al ., 2003). In the case of ATDs, they do not seem to be superior to APS in treating SAD depression, on the contrary, APS even seem to be more effective and better tolerated (Izáková et al ., 2009). We have also found no evidence on the use of BZD as an APS-potentiating treatment for SCZ and SAD but they seem to have a role in the treatment of agitated patients (Dold et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MS have been found to reduce relapses and hospitalizations (Greil et al ., 1997; Maj, 1988), to associate with lower total PANSS scores, and less negative and cognitive symptoms (Small et al ., 2003). In the case of ATDs, they do not seem to be superior to APS in treating SAD depression, on the contrary, APS even seem to be more effective and better tolerated (Izáková et al ., 2009). We have also found no evidence on the use of BZD as an APS-potentiating treatment for SCZ and SAD but they seem to have a role in the treatment of agitated patients (Dold et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, paliperidone extended-release, risperidone (Janicak et al ., 2001), ziprasidone (Keck et al ., 2001) and aripiprazole (Glick et al ., 2009) have all proven their effectiveness and safety in randomized clinical trials. Lithium (Greil et al ., 1997; Maj, 1988) and risperidone (Izáková et al ., 2009) have also shown effectiveness in open clinical trials, and finally, there are some observational studies for lithium and carbamazepine (Baethge et al ., 2004), clozapine (Ciapparelli et al ., 2003), risperidone (Vieta et al ., 2001) and long-acting risperidone injection (Lasser et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, we published the results of a study that monitored the use of various psychotropic drugs in patients with SAD, where we reported that combined therapy of antipsychotics with antidepressants occurred in 23.7% of patients, while mood stabilizers were used in 37.1% of cases [37]. Later on, we revealed the higher antipsychotic efficacy and tolerability of risperidone in comparison to haloperidol-sertraline combination for the acute treatment of SAD, depressed type [8]. Both treatments were comparable in terms of antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, less attention has been given to the treatment of SAD than that of schizophrenia. Although many efforts have been devoted to create therapeutic algorithms for the treatment of various mental disorders, guidelines specifically focused on the treatment of SAD are rarely reported in the literature [7] [8]. Moreover, there are significant limitations presented.…”
Section: Introductionmentioning
confidence: 99%